Preparation method of rosin-based super-hydrophobic anticorrosive coating with rapid photo-thermal self-repairing and self-cleaning functions

By using rosin polyol and fluorinel silane modified polydamine, prepare ultra -hydrophobic anticorrosive coating with light thermal self -repairing performance and self -cleaning function, solving the problem of unstable coating performance and oil resources consumption. The long -term durability and sustainable development of the coating are realized.

CN119371892APending Publication Date: 2025-01-28GUILIN UNIVERSITY OF TECHNOLOGY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411360555.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing photothermal superhydrophobic coatings have unstable performance after mechanical damage, and the widespread use of petroleum-based monomers accelerates the consumption of oil resources, affecting sustainable development.

Method used

Polybaramine modified by rosin -based polyol and fluorine -fluorine silane as the main raw material, through the coordinated reinforcement effect of dynamic covalent bonds and non -total price bonds, prepare ultra -hydrophobic anticorrosive coating with light thermal self -repairing performance and self -cleaning function Essence

Benefits of technology

The excellent light thermal self -repairing performance, self -cleaning function and good mechanical durability and chemical stability of the coating are realized, the use of the coating is extended, and the use of petrochemical resources has been reduced, which has sustainability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005064832100000091
    Figure BDA0005064832100000091
  • Figure HDA0005064832110000011
    Figure HDA0005064832110000011
  • Figure HDA0005064832110000012
    Figure HDA0005064832110000012
Patent Text Reader

Abstract

The invention discloses a preparation method of a rosin-based super-hydrophobic anticorrosive coating with rapid photo-thermal self-repairing and self-cleaning functions. The preparation method comprises the following steps: (1) modifying polydopamine by using trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane to obtain fluorine modified polydopamine microspheres; and (2) adding isophorone diisocyanate, polytetrahydrofuran, acrylic acid rosin and glycidyl methacrylate ester, dimethylglyoxime, adipic dihydrazide, the modified polydopamine microspheres and dibutyltin dilaurate into a reactor, and carrying out stepwise polymerization to obtain the rosin-based super-hydrophobic anticorrosive coating with rapid photo-thermal self-repairing and self-cleaning functions. The natural renewable resource rosin derivative is used for replacing partial petroleum-based raw materials, so that the cost can be effectively reduced, and the method is economical and environment-friendly; in addition, the prepared super-hydrophobic coating not only has excellent self-cleaning and anti-corrosion performance, but also has rapid photo-thermal self-repairing and recoverable performance, and has wide application in the field of intelligent anti-corrosion coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of super-hydrophobic coatings, and in particular to a method for preparing a rosin-based super-hydrophobic anti-corrosion coating with rapid photothermal self-repairing and self-cleaning functions. Background Art

[0002] Due to its excellent hydrophobicity, photothermal super-hydrophobic coatings have a wide range of applications in self-cleaning, anti-fouling, anti-icing / de-icing, and anti-corrosion. However, its surface structure is often fragile, has poor weather resistance, and is easily damaged by mechanical damage, which affects its performance stability and is not conducive to long-term use. Therefore, researchers have proposed a variety of methods to improve the durability and wear resistance of photothermal super-hydrophobic coatings, including introducing rigid monomers, adding nanoparticles to prepare composite materials, and giving materials self-healing properties. Among them, giving photothermal super-hydrophobic coatings self-healing properties is an effective way to extend the service life.

[0003] However, the current photothermal super-hydrophobic self-healing coating is mostly synthesized with petroleum-based monomers, and its widespread use will accelerate the consumption of decreasing petroleum resources, which is not conducive to social sustainable development. The preparation of photothermal super-hydrophobic self-healing coatings with renewable biomass resources instead of traditional petrochemical resources has attracted the attention of more and more researchers. Rosin is a rich natural renewable resource with a wide range of sources and low price. It has a rigid tricyclic phenanthrene skeleton in structure. After modification, it is introduced into the coating, which can significantly improve the adhesion, thermal stability and wear resistance of the coating. Therefore, the derivatives of rosin are introduced into the photothermal super-hydrophobic self-healing coating, and the synergistic strengthening effect of dynamic covalent bonds and non-covalent bonds is used to achieve the good adhesion of super-hydrophobic coatings to substrates, and its service life can be extended while the coating performance is kept stable. Summary of the invention

[0004] In view of the above technical problems, the present invention invents a method for preparing a rosin-based super-hydrophobic anti-corrosion coating, aiming to obtain a rosin-based super-hydrophobic anti-corrosion coating with excellent photothermal self-repairing performance and self-cleaning function.

[0005] To achieve the above purpose, the technical solution provided by the present invention is as follows:

[0006] A method for preparing a rosin-based super-hydrophobic anti-corrosion coating with photothermal self-repairing performance and self-cleaning function comprises the following steps:

[0007] (1) Fluoroalkylsilane modification of polydopamine: Fluoroalkylsilane was added to Tris-HCl buffer and ultrasonically treated for 30 min. Dopamine hydrochloride was then mixed with the above solution and stirred at 400 r / min at 50°C for 24 h. After the reaction was completed, polydopamine microspheres modified with fluoroalkylsilane were obtained by high-speed centrifugation, washing and vacuum drying.

[0008] (2) adding isophorone diisocyanate, polytetrahydrofuran, acrylic rosin and GMA ester and / or butanediol, a catalyst and an organic solvent into a reactor, introducing nitrogen to remove oxygen, stirring and reacting at 70° C. and 300 r / min for 2 h to obtain a polyurethane prepolymer solution;

[0009] (3) adding diacetyl oxime to the prepolymer solution of step (2) at 70° C. and stirring at 300 r / min for 1 h;

[0010] (4) lowering the temperature to 40° C., adding adipic acid dihydrazide and the fluoroalkylsilane-modified polydopamine microspheres obtained in step (1) to the solution in step (3) and reacting for 6 hours;

[0011] (5) The polymer solution obtained in step (4) is evenly coated on the surface of the substrate by a coating method, and dried at 90° C. for 24 h to obtain a rosin-based super-hydrophobic anti-corrosion coating having photothermal self-repairing properties and self-cleaning functions.

[0012] In step (1), according to the weight ratio, the fluoroalkyl silane is 2 parts, the Tris-HCl buffer is 100 parts, pH=8.5, and the dopamine hydrochloride is 2 parts; the fluoroalkyl silane is trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane.

[0013] In step (1), the centrifugal speed is 8000 r / min, the washing liquids are distilled water and acetone in sequence, the drying temperature is 40° C., and the drying time is 24 h.

[0014] In step (2), according to the weight ratio, isophorone diisocyanate is 100 parts, polytetrahydrofuran is 30 parts, acrylic rosin and GMA ester and / or butanediol are 5-20 parts, catalyst is 1 part, and solvent is 100 parts.

[0015] The molecular weight of the polytetrahydrofuran described in step (2) is 1000 g / mol.

[0016] The catalyst described in step (2) is dibutyltin dilaurate.

[0017] The organic solvent described in step (2) is N,N-dimethylacetamide or N,N-dimethylformamide.

[0018] In step (3), the amount of diacetyl oxime is 25 parts by weight.

[0019] In step (4), according to the weight ratio, adipic acid dihydrazide is 25 parts, and fluoroalkylsilane-modified polydopamine microspheres are 0.5-1.5 parts.

[0020] The stirring is mechanical stirring.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The raw materials of the method of the present invention are acrylic rosin and GMA esters as polyols and rigid monomers, dimethylglyoxime and adipic acid dihydrazide as dynamic monomers, and fluoroalkylsilane-modified polydopamine as hydrophobic monomers and photothermal agents. A rosin-based super-hydrophobic anticorrosion coating with excellent photothermal self-repairing performance and self-cleaning function is prepared by a simple one-pot method. The contact angle of the coating with water is as high as 163.1°, and it has outstanding hydrophobic properties, mechanical durability and chemical stability. Furthermore, the preparation method of the coating is simple, can be applied to substrates of different materials, and has broad application prospects in the field of intelligent anticorrosion coatings.

[0023] 2. The present invention utilizes rosin-based polyols to replace part of petroleum-based polyols to prepare super-hydrophobic coatings, which can reduce the use of petrochemical resources and is sustainable; in addition, the tricyclic phenanthrene skeleton in the natural renewable resource rosin has rigidity, and introducing it into the coating can significantly enhance the wear resistance and adhesion of the coating and extend its durability.

[0024] 3. The rosin-based super-hydrophobic coating provided by the present invention has outstanding photothermal conversion ability and self-repairing performance. The damage on the coating surface can be repaired by near-infrared light irradiation or heating, and has excellent durability and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a diagram showing the self-cleaning effect of the coating.

[0026] Figure 2 is the mechanical durability graph of the coating.

[0027] Figure 3 This is a diagram showing the self-healing effect of the coating.

[0028] Figure 4 is the polarization curve of the coating. DETAILED DESCRIPTION

[0029] The following is a detailed description in conjunction with the specific embodiments, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. The raw materials and reagents used in the examples are all commercially available unless otherwise specified.

[0030] The monomeric rosin ester RAG used in the examples was prepared according to the method described in application number CN105647389.

[0031] Example 1

[0032] (1) Fluoroalkylsilane modification of polydopamine: 2 parts of fluoroalkylsilane were added to 100 parts of Tris-HCl buffer (pH=8.5) and ultrasonically treated for 30 minutes. Then 2 parts of dopamine hydrochloride were mixed with the above solution and stirred at 400r / min at 50°C for 24 hours. After the reaction was completed, the polydopamine microspheres modified with fluoroalkylsilane were obtained by high-speed centrifugation at 8000r / min, washing with distilled water and acetone in turn, and vacuum drying at 40°C for 24 hours.

[0033] (2) 100 parts of isophorone diisocyanate and 30 parts of polytetrahydrofuran (M n =1000g / mol), 20 parts of acrylic rosin and GMA ester, 1 part of dibutyltin dilaurate and 100 parts of N,N-dimethylacetamide were added into the reactor, N2 was introduced for deoxygenation, and the mixture was stirred at 70°C and 300r / min for 2h to obtain a polyurethane (PU) prepolymer solution;

[0034] (3) At 70° C., 25 parts of diacetyl oxime were added to the prepolymer solution of step (2), and the mixture was stirred at 300 r / min for 1 h;

[0035] (4) lowering the temperature to 40° C., adding 25 parts of adipic acid dihydrazide and 1 part of the fluoroalkylsilane-modified polydopamine microspheres obtained in step (1) to the solution in step (3) and reacting for 6 hours;

[0036] (5) The polymer solution obtained in step (4) is evenly coated on the surface of the substrate by a coating method, and dried at 90° C. for 24 h to obtain a rosin-based super-hydrophobic anti-corrosion coating having photothermal self-repairing properties and self-cleaning functions.

[0037] Example 2

[0038] (1) Fluoroalkylsilane modification of polydopamine: 2 parts of fluoroalkylsilane were added to 100 parts of Tris-HCl buffer (pH=8.5) and ultrasonically treated for 30 minutes. Then 2 parts of dopamine hydrochloride were mixed with the above solution and stirred at 400r / min at 50°C for 24 hours. After the reaction was completed, the polydopamine microspheres modified with fluoroalkylsilane were obtained by high-speed centrifugation at 8000r / min, washing with distilled water and acetone in turn, and vacuum drying at 40°C for 24 hours.

[0039] (2) 100 parts of isophorone diisocyanate and 30 parts of polytetrahydrofuran (M n =1000g / mol), 20 parts of acrylic rosin and GMA ester, 1 part of dibutyltin dilaurate and 100 parts of N,N-dimethylacetamide were added into the reactor, N2 was introduced for deoxygenation, and the mixture was stirred at 70°C and 400r / min for 2h to obtain a polyurethane (PU) prepolymer solution;

[0040] (3) At 70° C., 25 parts of diacetyl oxime were added to the prepolymer solution of step (2), and the mixture was stirred at 300 r / min for 1 h;

[0041] (4) lowering the temperature to 40° C., adding 25 parts of adipic acid dihydrazide and 1.5 parts of fluoroalkylsilane-modified polydopamine microspheres obtained in step (1) to the solution in step (3) and reacting for 6 hours;

[0042] (5) The polymer solution obtained in step (4) is evenly coated on the surface of the substrate by a coating method, and dried at 90° C. for 24 h to obtain a rosin-based super-hydrophobic anti-corrosion coating having photothermal self-repairing properties and self-cleaning functions.

[0043] Example 3

[0044] (1) Fluoroalkylsilane modification of polydopamine: 2 parts of fluoroalkylsilane were added to 100 parts of Tris-HCl buffer (pH=8.5) and ultrasonically treated for 30 minutes. Then 2 parts of dopamine hydrochloride were mixed with the above solution and stirred at 400r / min at 50°C for 24 hours. After the reaction was completed, the polydopamine microspheres modified with fluoroalkylsilane were obtained by high-speed centrifugation at 8000r / min, washing with distilled water and acetone in turn, and vacuum drying at 40°C for 24 hours.

[0045] (2) 100 parts of isophorone diisocyanate and 30 parts of polytetrahydrofuran (M n =1000g / mol), 20 parts of acrylic rosin and GMA ester, 1 part of dibutyltin dilaurate and 100 parts of N,N-dimethylacetamide were added into the reactor, N2 was introduced for deoxygenation, and the mixture was stirred at 200r / min at 70°C for 2h to obtain a polyurethane (PU) prepolymer solution;

[0046] (3) At 70° C., 25 parts of dimethylglyoxime were added to the prepolymer solution of step (2), and the mixture was stirred at 200 r / min for 1 h;

[0047] (4) lowering the temperature to 40° C., adding 25 parts of adipic acid dihydrazide and 0.5 parts of fluoroalkylsilane-modified polydopamine microspheres obtained in step (1) to the solution in step (3) and reacting for 6 hours;

[0048] (5) The polymer solution obtained in step (4) is evenly coated on the surface of the substrate by a coating method, and dried at 90° C. for 24 h to obtain a rosin-based super-hydrophobic anti-corrosion coating having photothermal self-repairing properties and self-cleaning functions.

[0049] Example 4

[0050] (1) Fluoroalkylsilane modification of polydopamine: 2 parts of fluoroalkylsilane were added to 100 parts of Tris-HCl buffer (pH=8.5) and ultrasonically treated for 30 minutes. Then 2 parts of dopamine hydrochloride were mixed with the above solution and stirred at 400r / min at 50°C for 24 hours. After the reaction was completed, the polydopamine microspheres modified with fluoroalkylsilane were obtained by high-speed centrifugation at 8000r / min, washing with distilled water and acetone in turn, and vacuum drying at 40°C for 24 hours.

[0051] (2) 100 parts of isophorone diisocyanate and 30 parts of polytetrahydrofuran (M n =1000 g / mol), 5 parts of butanediol, 1 part of dibutyltin dilaurate and 100 parts of N,N-dimethylacetamide were added into the reactor, N2 was introduced for deoxygenation, and the mixture was stirred at 70°C and 300 r / min for 2 h to obtain a polyurethane (PU) prepolymer solution;

[0052] (3) At 70° C., 25 parts of diacetyl oxime were added to the prepolymer solution of step (2), and the mixture was stirred at 300 r / min for 1 h;

[0053] (4) lowering the temperature to 40° C., adding 25 parts of adipic acid dihydrazide and 1.5 parts of fluoroalkylsilane-modified polydopamine microspheres obtained in step (1) to the solution in step (3) and reacting for 6 hours;

[0054] (5) The polymer solution obtained in step (4) is evenly coated on the surface of the substrate by a coating method, and dried at 90° C. for 24 h to obtain a rosin-based super-hydrophobic anti-corrosion coating having photothermal self-repairing properties and self-cleaning functions.

[0055] Comparison Example

[0056] (1) 100 parts of isophorone diisocyanate and 30 parts of polytetrahydrofuran (M n =1000g / mol), 20 parts of acrylic rosin and GMA ester, 1 part of dibutyltin dilaurate and 100 parts of N,N-dimethylacetamide were added into the reactor, N2 was introduced for deoxygenation, and the mixture was stirred at 70°C and 300r / min for 2h to obtain a polyurethane (PU) prepolymer solution;

[0057] (2) At 70° C., 25 parts of dimethylglyoxime were added to the prepolymer solution of step (1), and the mixture was stirred at 300 r / min for 1 h;

[0058] (3) lowering the temperature to 40° C., adding 25 parts of adipic acid dihydrazide to the solution of step (2) and reacting for 6 hours;

[0059] (4) The polymer solution obtained in step (3) is evenly coated on the surface of the substrate by a coating method, and dried at 90° C. for 24 h to obtain a rosin-based anti-corrosion coating with self-healing properties.

[0060] Implementation Effect

[0061] (1) The coating obtained in Example 1 has a smooth surface and good bonding strength with the substrate; the tensile strength reaches 25.3 MPa, the elongation at break is 956%, and the water contact angle is 158.6°.

[0062] The self-cleaning property of the super-hydrophobic coating is to place sand on the surface of the coating and observe how clean the sand is after the water drops. When water is dripped on the surface of the super-hydrophobic coating sprinkled with sand, the water drops roll down in a ball shape, and at the same time, the sand adheres to the water drops and rolls off, showing an excellent self-cleaning effect (see Figure 1 ).

[0063] (2) The coating obtained in Example 2 has a smooth surface and good bonding strength with the substrate; the tensile strength reaches 33.6 MPa, the elongation at break is 624%, and the water contact angle is 163.1°.

[0064] The mechanical durability of the superhydrophobic coating was characterized by sand impact test, water flow impact test, sandpaper abrasion test and tape stripping test. Sand impact test: The coating was tilted at 45°, and sand (80-120 mesh) impacted the coating from a height of 50 cm. The water contact angle of the coating was measured after every 20 g of sand impact. Water flow impact test: The coating was tilted at 45° and impacted with a water flow from a height of 40 cm. The water contact angle of the coating was measured after every 500 mL of water flow impact. Sandpaper abrasion test: The coating was inverted, and then a 50 g weight was placed on the glass plate. The coating was moved parallel to the 1000 mesh sandpaper for a reciprocating motion of 15 cm. The water contact angle of the coating was measured every 10 reciprocating motion cycles. Tape stripping test: Ordinary double-sided tape was adhered to the coating and then peeled off. The water contact angle of the coating was measured after each 10 times of tape stripping.

[0065] The water contact angle of the coating after being impacted by 200g sand was 151.4° (see Figure 2 a), after 5L water impact, the water contact angle is 151.2° (see Figure 2 b), after 100 reciprocating wear cycles, the water contact angle is 152.4° (see Figure 2 c), after 100 tape peelings, the water contact angle was 151.4° (see Figure 2 d), it can be seen that the coating has excellent mechanical durability.

[0066] (3) The coating obtained in Example 3 has a smooth surface and good bonding strength with the substrate; the tensile strength reaches 9.2 MPa, the elongation at break is 1008%, and the water contact angle is 136.6°.

[0067] The self-healing property of the superhydrophobic coating was demonstrated by scratching the coating surface with a razor blade and then irradiating it with near-infrared light (λ = 808 nm, 0.5 W cm -2 ) to observe the repair of scratches.

[0068] After the coating was irradiated with near-infrared light for 30 seconds, the surface temperature reached 138.5°C and the scratches were completely repaired, indicating that the coating has excellent photothermal conversion and self-healing capabilities (see Figure 3 ).

[0069] (4) The coating obtained in Example 4 has a smooth surface and good bonding strength with the substrate; the tensile strength reaches 28.0 MPa, the elongation at break is 557%, and the water contact angle is 154.0°.

[0070] The coating was immersed in a 3.5 wt % sodium chloride solution for 30 min, and then the polarization curve was tested using an electrochemical workstation to study the anti-corrosion performance of the coating.

[0071] Corrosion current density and corrosion potential are important parameters to measure the corrosion resistance of coatings. The corrosion current density and corrosion potential of blank tinplate are 1.620×10 -5 A cm -2 and -0.9315V. In comparison, the tinplate coated with the polymer solution has a smaller corrosion current density (5.877×10 -9 A cm -2 ), the corrosion potential is also closer to a positive value (-0.1475 V), indicating that the coating has a significant protective effect on the substrate (see Figure 4 ).

[0072] (5) The coating obtained in the control example has a smooth surface and good bonding with the substrate; the tensile strength is 2.8 MPa, the elongation at break is 973%, and the water contact angle is 105.7°. It is recyclable, but has no photothermal self-healing properties and poor anti-corrosion properties (Table 1).

[0073] In summary, the present invention prepares a rosin-based super-hydrophobic anticorrosion coating with excellent photothermal self-repairing performance and self-cleaning function by a simple one-pot method. Due to the rigid tricyclic phenanthrene structure of rosin, the obtained coating has good bonding with the substrate and exhibits excellent wear resistance. At the same time, based on the excellent hydrophobicity and photothermal conversion ability of polydopamine modified by fluoroalkyl silane, the obtained coating exhibits outstanding self-cleaning performance and photothermal self-repairing performance, extending the service life of the coating. The preparation of a super-hydrophobic coating using rosin-based polyols to replace part of petroleum-based polyols has the advantages of simple operation and sustainability, and can significantly increase the added value of rosin and enhance the comprehensive performance of the coating.

[0074] Table 1 Product form and related performance data

[0075]

Claims

1. A method for preparing a rosin-based super-hydrophobic anti-corrosion coating with rapid photothermal self-repairing and self-cleaning functions, characterized in that: The following steps are included: (1) Modification of polydopamine microspheres: Add fluoroalkyl silane to Tris-HCl buffer and ultrasonicate for 30 min. Then mix dopamine hydrochloride with the above solution and stir at 400 r / min at 50°C for 24 h. After the reaction is completed, high-speed centrifugation, washing and vacuum drying are performed to obtain polydopamine microspheres modified with fluoroalkyl silane. (2) adding isophorone diisocyanate, polytetrahydrofuran, ester of acrylic rosin and glycidyl methacrylate (GMA) and / or butanediol, a catalyst and an organic solvent into a reactor, introducing nitrogen to remove oxygen, stirring at 70° C. and 300 r / min for 2 h to obtain a polyurethane (PU) prepolymer solution; (3) adding diacetyl oxime to the prepolymer solution of step (2) at 70° C. and stirring at 300 r / min for 1 h; (4) lowering the temperature to 40° C., adding adipic acid dihydrazide and the fluoroalkylsilane-modified polydopamine microspheres obtained in step (1) to the solution in step (3) and reacting for 6 hours; (5) The polymer solution obtained in step (4) is evenly coated on the surface of the substrate by a coating method, and dried at 90° C. for 24 h to obtain a rosin-based super-hydrophobic anti-corrosion coating having photothermal self-repairing properties and self-cleaning functions.

2. The preparation method according to claim 1, characterized in that: In step (1), according to the weight ratio, the fluoroalkyl silane is 2 parts, the Tris-HCl buffer is 100 parts, pH=8.5, and the dopamine hydrochloride is 2 parts; the fluoroalkyl silane is trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane.

3. The preparation method according to claim 1, characterized in that: In step (1), the centrifugal speed is 8000 r / min, the washing liquids are distilled water and acetone in sequence, the drying temperature is 40° C., and the drying time is 24 h.

4. The preparation method according to claim 1, characterized in that: In step (2), according to the weight ratio, isophorone diisocyanate is 100 parts, polytetrahydrofuran is 30 parts, acrylic rosin and GMA ester and / or butanediol are 5-20 parts, catalyst is 1 part, and solvent is 100 parts.

5. The preparation method according to claim 1, characterized in that: The molecular weight of the polytetrahydrofuran described in step (2) is 1000 g / mol.

6. The preparation method according to claim 1, characterized in that: The catalyst described in step (2) is dibutyltin dilaurate.

7. The preparation method according to claim 1, characterized in that: The organic solvent described in step (2) is N,N-dimethylacetamide or N,N-dimethylformamide.

8. The preparation method according to claim 1, characterized in that: In step (3), the amount of diacetyl oxime is 25 parts by weight.

9. The preparation method according to claim 1, characterized in that: In step (4), according to the weight ratio, adipic acid dihydrazide is 25 parts, and fluoroalkyl silane-modified polydopamine microspheres are 0.5-1.5 parts.

10. The preparation method according to claim 1, characterized in that: The stirring is mechanical stirring.

Citation Information

Patent Citations

  • Method for preparing rosin-based IPDI (isophorone diisocyanate)-type polyurethane prepolymers

    CN105646822A

  • High-strength wet strength agent for papermaking and preparation method of wet strength agent

    CN110004767A

  • Preparation method of photo-thermal ice-resistant super-hydrophobic coating and super-hydrophobic coating thereof

    CN118496751A